Factor each trinomial: x2 + 4x + 3 (x + 3)(x + 1)
Factor each trinomial: x2 - 2x - 3 (x – 3)(x + 1)
Factor each trinomial: x2 + 9x + 20 (x + 4)(x + 5)
Factor each trinomial: x2 – 14x + 24 (x – 2)(x – 12)
Factor each trinomial: x2 – 20x + 64 (x – 4)(x – 16)
Factor each trinomial: x2 - 5xy + 6y2 (x – 2y)(x – 3y)
Factor each trinomial: x2 + xy – 12y2 (x + 4y)(x – 3y)
Factor each trinomial and then solve: x2 – 4x – 5 = 0 (x + 1)(x – 5) = 0 x = -1 and 5
Factor each trinomial and then solve: x2 + 4x – 12 = 0 (x + 6)(x – 2) = 0 x = -6 and 2
Factor each trinomial and then solve: x2 + 8x + 12 = 0 (x + 6)(x + 2) = 0 x = -6 and -2
Factor each trinomial and then solve: x2 – 10x + 16 = 0 (x – 8)(x – 2) = 0 x = 8 and 2
Factor each trinomial and then solve: x2 + 14x + 33 = 0 (x + 11)(x + 3) = 0 x = -11 and -3
Factor each trinomial and then solve: x2 + 4x – 45 = 0 (x + 9)(x – 5) = 0 x = -9 and 5
Now start your homework … THE END Now start your homework …